Influencing factors of suicidal ideation in lung cancer patients in Midland China: A mixed-method study - Yu, Ting; Hu, Deying; Jiang, Yan; Wang, Cong; Liu, Shanshan (Frontiers in Psychiatry, 2023)
Introduction The suicide risk of lung cancer patients is higher than that of patients with other cancers. However, as China is a large country for lung cancer, there are no relevant reports on lung cancer suicides. This study aimed to investigate the prevalence of suicidal ideation and explore its influencing factors in lung cancer patients. Methods In this cross-sectional study, between July to November 2019, 366 lung cancer patients from the oncology department of a general hospital in Wuhan were chosen as participants. Of these, eight with lung cancer and suicidal ideation were selected for in-depth interviews. Results A total of 22.68% of lung cancer patients reported suicidal ideation. Sex, cancer stage, number of uncomfortable symptoms, and satisfaction with treatment were independently associated with suicidal ideation. This qualitative study found that the experience of suicidal ideation in lung cancer patients includes physiological (heavy burden of symptoms),psychological (bad mood, thwarted belongingness, perceived burdensomeness, and stigma), and social factors (high economic pressure and negative life events). Discussion These findings suggest that the incidence of suicidal ideation in lung cancer patients is higher than that of other cancers and is affected by many factors. Therefore, there should be routine screening and assessment of suicidal ideation among lung cancer patients, and related mental health and suicide prevention education should be provided.